A Re-investigation: Effect of various parameter on mechanical properties of copper matrix composite fabricated by powder metallurgy. (2021) - Ankur,; Bharti, Ajaya; Prasad, Devendra; Kumar, Naveen; Saxena, Kuldeep K.
Abstract: In this study, a re-investigation on metal matrix composite fabricated by powder metallurgy route has been done. Copper based metal matrix composite has the wide applications because of their good electrical, thermal and mechanical properties. Copper has good strength and resistance to corrosion. But in order to increase the properties of copper, copper matrix composite has been fabricated by powder metallurgy process. The composites materials fabricate by powder metallurgy process has various property such as hardness, tensile strength, compressive strength, toughness, fatigue strength. These properties depend on some parameter such as reinforcement, pressure during powder compaction, temperature of sintering, holding time at sintering temperature, particle size, volume fraction of reinforcement etc. This study shows investigation of effect of various parameter on mechanical property of copper-based metal matrix composites. It has shown that due to presence of secondary phase hard particle like alumina, SiC, titanium carbide, TiO2 in copper metal matrix increase hardness, strength and reduce density. Reduction in density is very important in order to fabrication of automobile and aircraft parts. The strength and hardness increase with addition of SiC but ductility is reduced. It is shown that sintering temperature and sintering time is most important parameter because it highly influences hardness and strength.